PEMIJAHAN DAN PENJINAKAN IKAN PANTAU (Rasbora latestriata) - Ahmad, Muchtar; Nofrizal, Nofrizal (Jurnal Perikanan dan Kelautan, 2011)
Studies on Rasbora sp. have been developed in the last two decades, but nostudy have been conducted on the fish spawning related to requirement of adomesticated fish (normal movement, feed on artificial food, growth, and spawn).An experiment on the ethology of R. latestriata executed in the concrete tank of3mx2mx15m watered continuously up to 50 cm in depth and by inlet pipe positionthe water move at the flow speed less than 10 cm/sec. More than 60 randomly maleand female fishes feed ‘ad libitum’ with catfish pellet artificial food and cultured forthree months in the rainy season. At the third month approximately hundred fishlarvae of 1 to 1.5 cm were found. This study concluded that Rasbora can be culturedcommercially, as the fish domesticated as ob-served moving normally, feedingartificial food, growth and spawn in the human control environment. However,further study on breeding and commercial aquaculture of the fish is necessary.